Depositional environment of the early Pleistocene Castlepoint Formation, New Zealand: a canyon fill in situ. Issue 4 (2nd October 2018) - Buckeridge, John S.; Beu, Alan G.; Gordon, Dennis P.
ABSTRACT: The early Pleistocene (early Nukumaruan) Castlepoint Formation cropping out on the Wairarapa coast contains a diverse molluscan, bryozoan and barnacle assemblage, with a few brachiopods, corals, echinoids, crabs and polychaetes, comprising mixed warm- and cool-water taxa and outer shelf and shallow-water taxa. Sedimentary structures within the beds (fluid release structures, steep original dips, large load casts, displaced blocks) confirm a dynamic depositional setting by gravity sliding into what is interpreted as a canyon head. The barnacle- and bryozoan-rich molluscan coquina (barnamol and bryomol) that makes up much of the Castlepoint Formation comprises thanatocoenoses resulting from transportation of shallow-water elements, which accumulated deeper-water taxa in transit, to settle in a shelf-edge canyon environment. We interpret all stratigraphic contacts as sedimentary ones; the formation is essentially a canyon fill in situ .